Seismic displacement charts for the performance-based assessment of reinforced soil walls. Issue 4 (1st August 2005) - Wang, W. C.; Huang, C. C.
Abstract : This paper presents a pseudo-static-based approach for evaluating the mechanical effects of facing components on the seismic displacement of reinforced soil walls backfilled with cohesionless soils. The proposed method is used to examine some factors that may influence the seismic stability and/or displacement of a 5 m high idealized wall, such as the connection strength at the facing–soil interface, the shear strength of the facing, the shear strength of the backfill soils, and the length of the reinforcement. Seismic displacement charts are established for a 5 m high idealized reinforced wall with various types of facing subjected to four different ground excitations. These charts are then verified using wall displacements measured after a major earthquake, and can be used to facilitate preliminary performance-based seismic designs of reinforced soil walls. Analytical results show that a conventional 'two-wedge' analysis greatly underestimates the seismic stability of a wall with a structural facing component because the interaction between the facing and the retained soils is ignored. The connection strength between the facing and the reinforcement may significantly increase the seismic stability and/or reduce the seismic displacement of the investigated wall provided that a specially designed facing–geogrid connection is used, which enables very high connection strength to be developed. The interblock shear strength of discrete-type facing affects the seismic stability of the wall only in a secondary way, because higher interblock shear strength may cause a failure mechanism that passes through the bottom of the wall. The unit weight of the facing plays a moderate role in the increase of the seismic stability of the 5 m high wall with vertical facing. It is also shown that the advantage of using a structural facing may vary according to changes in the internal friction angle of the backfill and the length of reinforcing material.